2016
DOI: 10.1039/c6ra11106h
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional iron oxide/graphene aerogel hybrids as all-solid-state flexible supercapacitor electrodes

Abstract: Three dimensional iron oxide/graphene aerogel hybrid (Fe2O3/GA) was synthesized and used as electrode materials in flexible supercapacitor devices, which show high specific capacitance of 440 F g−1 with 89% capacitance retention after 2200 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 53 publications
0
46
3
Order By: Relevance
“…These are higher than the previous studies reported, [62][63][64][65][66] such as Co 9 S 8 //AC. NC@CoSe 2 //Co-NC@Fe 2 O 3 shows the maximum power density of 8.9 kW/kg at an energy density of 14 Wh/kg.…”
Section: Electrochemical Propertiescontrasting
confidence: 70%
“…These are higher than the previous studies reported, [62][63][64][65][66] such as Co 9 S 8 //AC. NC@CoSe 2 //Co-NC@Fe 2 O 3 shows the maximum power density of 8.9 kW/kg at an energy density of 14 Wh/kg.…”
Section: Electrochemical Propertiescontrasting
confidence: 70%
“…In the faradaic process, energy storage occurs via electron transfer across the electrolyte‐electrode interface, due to the rapid and reversible reduction/oxidation (redox) processes of the specific materials supported on the electrode surface; such materials are also known as pseudocapacitors . In the non‐faradaic process, however, the energy storage occurs via frequent adsorption/desorption of charged electrolyte ions on the tiny surface of the electrode; no charge transfer occurs . In both of these processes, the electrode material has the main effect on the efficiency of the capacitor.…”
Section: Figurementioning
confidence: 99%
“…Supercapacitors [1] are energy storage devices, also known as electric double-layerc apacitors, that have wide appeal for their massivep owerd ensities, operation over ab road range of temperatures, extra-long life times, and high reversibility.A ccording to the nature of the electrode material and the mechanism of energy storage, supercapacitors can store energy through either faradaic or non-faradaic processes. [2,3] In the faradaic process, energy storage occurs via electron transfer across the electrolyte-electrode interface, due to the rapid and reversible reduction/oxidation( redox) processes of the specific materials supported on the electrode surface;s uch materials are also knowna sp seudocapacitors. [4] In the non-faradaic process, however,t he energy storage occurs via frequenta dsorption/ desorption of charged electrolyte ions on the tiny surface of the electrode;n oc harget ransfer occurs.…”
mentioning
confidence: 99%
“…With regard to the latter, carbon/metal oxide nanocomposites have been extensively investigated as active materials for charge storage schemes . By integrating metal oxides and carbon the advantages of both materials including high surface area, high conductivity, improved capacitance or energy density and in some cases even higher rate capability and cycling stability can be simultaneously utilized . Pure metal oxide based electrodes typically show low conductivities and stability as well as low surface area .…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide nanoparticles are incorporated into carbon electrodes by, for example, chemical reduction of graphene oxide in the presence of an Fe(III) salt at elevated temperatures . The resulting Fe 3 O 4 or Fe 2 O 3 nanoparticles are attached to the rGO sheets . In another example, initially grown FeOOH nanorods were electrochemically transformed into Fe 3 O 4 nanoparticles covering the rGO surface .…”
Section: Introductionmentioning
confidence: 99%